The Nature of Environmental Violence in Climate Change: Considering the Perspective of Muslim Civil Society in Banyumas - Khashogi, Luqman Rico (International Journal of Social Science and Religion (IJSSR), 2024)
The multi-impact environmental damage that has an impact on climate change is the result of the lack of equitable distribution of utilization and control of resources due to the hegemony of power and authority forcing people to exploit nature. Poor environmental governance, which later became a source of crime and suffering for the community, was dominantly the result of the behavior (violence) of the authorities rather than the community’s low awareness and literacy. In Banyumas, climate balance is also an essential issue. This study aimed to find answers to whether the Young Muslim Civil Society in Banyumas has concerns about climate change and its governance. The UNICEF survey in 2021 stated that the younger generation in Indonesia has empathy for environmental governance. This study was field research with a sociological approach through the paradigm developed by Jamil Salmi about violence maps; direct violence, indirect violence (violence by omission), repressive violence, and alienation violence. To map their views, I collected 304 randomly selected samples for filling out a questionnaire based on direct validity and test-retest reliability indicators. According to the discourse of young Muslim Civil Society in Banyumas, this study indicated that repressive violence was an essential part of the nature of environmental violence in climate change. The Young Muslim Civil Society in Banyumas was overwhelmed with worries, which should encourage them not to let state administrators put forward desertion in responding to the global challenge; climate change.